Analisis Semiotika Teori Roland Barthers pada Iklan “ Al Baik” : Makna Visual - Afriana Afriana; Fatimatuzzahra Nasution; Nuzul Hasby; Ahmad Zulfadli (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to analyze the visual meaning in Al Baik advertisements on Instagram featuring food and beverages. Using Roland Barthes' semiotic approach, this research examines visual elements such as images, colors, text, and composition to understand the messages conveyed. The research method used is descriptive qualitative. The results show that the visual elements in Al Baik advertisements not only depict food products, but also convey cultural values such as national pride, warmth of tradition, and affordability. Instagram as a social media platform has proven effective in conveying these messages through attractive and meaningful visuals. This research reveals how modern advertising can serve as a promotional tool as well as a means of cultural communication that is relevant in the digital age.